Cutaneous manifestations of autoimmune polyglandular syndrome type 1 - case report and literature review - Julita A. Krahel; Anna Baran; Iwona Flisiak (Termedia Publishing House, 2016)
Introduction. Autoimmune polyglandular syndrome type 1 (APS-1) is a type of polyendocrinopathy, inherited in an autosomal recessive manner. Beside the classic triad of symptoms (candidiasis of the skin and mucous membranes, hypoparathyroidism and Addison's disease), other skin and systemic diseases may be present. Objective . To present a patient with history of APS-1, in whom in addition to the classic triad of symptoms vitiligo, alopecia, and dental enamel hypoplasia and nail dystrophy were observed. Case report . A 43-year-old patient, with a history of APS-1 syndrome, was admitted to the hospital because of exacerbation of candidiasis of the mucous membranes of the mouth. Additionally, dystrophy of the nails and the dental enamel, generalized alopecia and extensive vitiligo were observed. Due to antifungal treatment partial clinical improvement was achieved. Conclusions . APS-1 is a potentially life-threatening complex set of symptoms. Consistent treatment and strict follow-up of patients with this syndrome are necessary.